Panel Modelling to Analyze Financial Performance : Evidence on Islamic Commercial Bank in Indonesia: Pemodelan Panel untuk Menganalisis Kinerja Keuangan: Bukti pada Bank Umum Syariah di Indonesia - M Aji; Fuad Hasyim; Nida Kusuma Hameida (Jurnal Ilmu Perbankan dan Keuangan Syariah, 2023)
Financial performance is a vital instrument in profit-making in the banking sector, therefore maintaining optimal is a must for banks to get maximum profit. This study aims to analyze the influence of financial performance instruments with CAR, NPF, OCR, and DER proxies on return on assets (ROA) in Islamic Commercial Banks (BUS). This research was conducted on Islamic Commercial Banks for 2016-2020. The sampling method used was purposive sampling method with a total samples 12 of Islamic Commercial Banks. The data used secondary data in the form of financial resports that published by Otoritas Jasa Keuangan (OJK) through the website www.ojk.go.id. The analytical method used multiple linear regressions of panel data with a Fixed Effect Model (FEM) selection using EVIEWS 10 statistic tool. The results show that the CAR, NPF, OCR, and DER variables have an effect on ROA.